2021
DOI: 10.1016/j.echo.2021.01.004
|View full text |Cite
|
Sign up to set email alerts
|

The Pathophysiological Link between Right Atrial Remodeling and Functional Tricuspid Regurgitation in Patients with Atrial Fibrillation: A Three-Dimensional Echocardiography Study

Abstract: Background: Atrial fibrillation (AF) itself may lead to functional tricuspid regurgitation (FTR) through tricuspid annulus (TA) dilation. However, the pathophysiological determinants of TA enlargement in AF patients remain to be clarified. The objectives of this study were (1) to compare the TA size and function in AF patients versus healthy subjects; (2) to identify the determinants of TA remodeling in patients with AF and FTR;and (3) to assess the relationships among right heart structures and severity of FT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
50
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 29 publications
5
50
1
1
Order By: Relevance
“…Notably, however, atrial volumes were independent determinants of annular areas, whereas ventricular volumes were not. These results resonate with recent publications showing that the RA dilation is the major determinant of TA size in patients with atrial fibrillation and/or functional TR (20,21). Longitudinal studies with long-term follow-up are required to establish the (patho)physiological link between exercise-induced cardiac remodeling, functional valvular regurgitation, and, eventually, occurrence of atrial fibrillation.…”
Section: Discussionsupporting
confidence: 86%
“…Notably, however, atrial volumes were independent determinants of annular areas, whereas ventricular volumes were not. These results resonate with recent publications showing that the RA dilation is the major determinant of TA size in patients with atrial fibrillation and/or functional TR (20,21). Longitudinal studies with long-term follow-up are required to establish the (patho)physiological link between exercise-induced cardiac remodeling, functional valvular regurgitation, and, eventually, occurrence of atrial fibrillation.…”
Section: Discussionsupporting
confidence: 86%
“…It has been recognized that TA diameter change is an independent FTR contributory factor. Since this study is a retrospective one, it is not considered a routine preoperative measurement parameter, though LATD and LALD can indirectly reflect TA expansion extent [Guta 2021]. In fact, our results demonstrated that no correlation between pre-surgery atrial size in multivariate analysis and long-term S-FTR likelihood is present, which is supported by other researchers, such as David et al [David 2018].…”
Section: Discussionsupporting
confidence: 74%
“…In dTGA, correlations seem to have disappeared, which could partially explain accompanying tricuspid functional regurgitations. In earlier studies, TA abnormalities were found to be associated with atrial volumes as well, which effects could not be excluded in dTGA patients either (19).…”
Section: Discussionmentioning
confidence: 90%